O papel do aleitamento materno na redução da mortalidade infantil no Brasil de 1986 a 2006 - Figueiredo, Carlos Eduardo da Silva (2017)
Objectives: This study evaluated the breastfeeding influence in the coefficient of infant mortality and socio-environmental, demographic, prenatal and childbirth care and immunobiologicals use present in the immunization schedule of the Brazilian National Immunization Program contribution in infant mortality, in the period between 1986 and 2006. Metodology: Data were collected from Demographic Health Survey, performed in Brazil in 1986, 1991 and 2006. After selection, the variables were analyzed for association with the outcome (death under one year old). Multivariate analysis was performed using binary logistic regression (software SPSS). After model adjustment, it was possible to identify the variables that best predict the occurrence of death in children under one year old. Results: It was demonstrated that breastfeeding has a protective effect on death in children under one year old. Maternal schooling, water and sewage network at home, number of pre-natal consultations, place of children’s birth and children’s vaccination status also are able to explain the outcome. Limitations: Due to the different objectives of the surveys carried out in the years mentioned above, the records are not standardized. This fact makes it difficult sometimes to demonstrate those variable’s contribution over time. Another limitation was the impossibility of assessing the causality between death and time of breastfeeding. Practical contribution: Improve policies to encourage breastfeeding. Social contributions: Encouragement of breastfeeding. Originality: This study is original since evaluates data incompassing so years.